Overcoming dengue vaccine challenges through next-generation virus-like particle immunization strategies - Parra-González, Mariana; Nájera-Maldonado, Lucio; Peralta-Cuevas, Esperanza; Gutierrez-Onofre, Ashley J.; Garcia-Atutxa, Igor; Villanueva-Flores, Francisca (Frontiers in Cellular and Infection Microbiology, 2025)
Dengue fever represents an escalating global health threat, as unprecedented outbreaks expose significant limitations of current vaccine strategies. Conventional live-attenuated dengue vaccines, while partially efficacious, face critical hurdles including serotype imbalances and antibody-dependent enhancement (ADE). This review critically assesses virus-like particle (VLP) vaccines as a promising alternative, providing safer, non-replicating platforms that mimic viral structure without risks associated with live replication. Technological advancements in recombinant expression systems have improved VLP yield, stability, and scalability, addressing deployment obstacles. Recent preclinical studies demonstrate that tetravalent dengue VLP vaccines induce balanced neutralizing antibodies across all serotypes, effectively circumventing ADE in animal models. These findings suggest superior safety and robust immune responses, potentially surpassing live-attenuated and mRNA-based vaccines. We emphasize advancements in VLP vaccine technology, including novel tetravalent particle designs engineered to exclude ADE-related immunopathogenic components (prM protein), innovative stability-enhancing formulation techniques, and cost-effective recombinant production platforms (yeast and plant-based systems). Additionally, this review proposes novel deployment strategies, such as regional manufacturing hubs, standardized modular VLP platforms, adaptive clinical trial frameworks leveraging surrogate endpoints, and strengthened international coordination for equitable vaccine distribution. Integrating these scientific innovations and practical strategies positions dengue VLP vaccines as pivotal next-generation solutions for global dengue prevention.